(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Advertising is a powerful tool of communication force, highly visible that helps to sells goods, services, and ideas etc. Advertising reflects the need of the times, whether we like it or not advertisements are seen everywhere. Although Advertising holds just one part of the entire promotional mixture, it is mostly regarded as the main face of a holistic marketing combination campaign set-up. Promotion or advertisement is the collaboration of all endeavors began by sellers for establishing information sources or outlets as well as continuation to augment the intensity of a particular commodity or service. In this paper we will use secondary data approach. The result of the study shows that ASCI have adopted a code for self-regulation in advertising in FMCG. The code is a commitment, a promise, to honest advertising and to fair competition in the market. Thus, the thinking among the advertising fraternity in FMCG was “Regulate yourself, or someone else will”.